A case of secondary erythromelalgia with perivascular and intramural mucin. (10th October 2014) - Blake, Tristan; Mortimore, Rohan; De Ambrosis, Kathryn
Abstract: We present a 49‐year‐old man with type I erythromelalgia, demonstrating a newly reported histological feature of striking perivascular mucin. There is a single previously reported case in the literature describing these histological features. This patient had a comorbid history of primary myelofibrosis diagnosed 2 years prior to his presentation.